Analisis Faktor Faktor Kecelakaan Kerja pada Pekerja Tambang: Literature Review - Aliyah Rifdha; Susilawati Susilawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Accident cases in Indonesia are still relatively high and continue to increase every year. Of the various employment sectors, mining is considered an important source of income globally. Mining is one of the most dangerous work sectors in the world, having major consequences and the risk of accidents for workers. The aim of this literature review is to analyze the factors that cause work accidents in mining. The method used is a systematic literature review. The data was obtained from various journals in electronic databases obtained from Google Scholar. The collected data is then analyzed carefully. The results of the analysis from these journals showed that the factors causing work accidents in mining workers were mostly caused by human factors (Unsafe Action). both on worker knowledge, worker skills and worker attitudes who do not comply with standard operational procedures in the work environment, then followed by environmental factors (unsafe conditions) and equipment factors.